Nationwide seroprevalence of SARS-CoV-2 during the COVID-19 pandemic and prepandemic periods in Lao PDR - Koukeo Phommasone; Chanthala Souksakhone; Anisone Chanthongthip; Ooyanong Phonemixay; Chirapha Keokhamphoui; Stéphane Priet; Karine Barthélémy; Xavier de Lamballerie; Manivanh Vongsouvath; Elizabeth A. Ashley; Audrey Dubot-Pérès (PLoS ONE, 2025)
Background Lao PDR reported a low number of confirmed SARS-CoV-2 cases until the introduction of COVID-19 vaccines in April 2021. This raised doubts about whether the reported number reflected the true situation and questioned about possible pre-existing immunity against SARS-CoV-2. Methods We retrospectively analyzed leftover blood donor samples collected in 2003–2004, 2015, and 2018 in Vientiane Capital, as well as samples collected in 2020 and between February and August 2021 across 18 provinces in Lao PDR to better understand the epidemiology of the infection. The samples were first screened using an anti-SARS-CoV-2 IgG ELISA (Euroimmun). The presence of anti-SARS-CoV-2 antibodies was then confirmed or refuted by testing positive and equivocal samples using anti-SARS-CoV-2 IgG CLIA (Beckman Coulter) targeting anti-Spike antibodies and SARS-CoV-2 virus neutralization test. Results All pre-pandemic sera from Vientiane capital (79 in 2003−2004, 406 in 2015 and 191 in 2018), and all 2,225 sera collected in 2020 from eight provinces, tested negative. A total of 3,663 sera were collected prospectively in 2021 from 14 provinces. Bokeo and Oudomxay had the highest prevalence, each at 19.8%, followed by Luang Namtha at 16.1% and Salavan at 15.5%. However, the majority of samples collected from those four provinces were obtained after the outbreak surge and the introduction of COVID-19 vaccines in mid-April. Conclusion There was no evidence of cross-reactive neutralizing antibodies prior to the COVID-19 pandemic and the seroprevalence of SARS-CoV-2 was confirmed to be low in Lao PDR before the introduction of COVID-19 vaccines and the surge in infections from May 2021.